DNA Methylation Age and Physical and Cognitive Aging. (20th October 2019) - Maddock, Jane; Castillo-Fernandez, Juan; Wong, Andrew; Cooper, Rachel; Richards, Marcus; Ong, Ken K; Ploubidis, George B; Goodman, Alissa; Kuh, Diana; Bell, Jordana T; Hardy, Rebecca
Abstract: Background: DNA methylation (DNAm) age acceleration (AgeAccel) has been shown to be predictive of all-cause mortality but it is unclear what functional aspect(s) of aging it captures. We examine associations between four measures of AgeAccel in adults aged 45–87 years and physical and cognitive performance and their age-related decline. Methods: AgeAccelHannum, AgeAccelHorvath, AgeAccelPheno, and AgeAccelGrim were calculated in the Medical Research Council National Survey of Health and Development (NSHD), National Child Development Study (NCDS) and TwinsUK. Three measures of physical (grip strength, chair rise speed, and forced expiratory volume in one second [FEV1 ]) and two measures of cognitive (episodic memory and mental speed) performance were assessed. Results: AgeAccelPheno and AgeAccelGrim, but not AgeAccelHannum and AgeAccelHorvath were related to performance in random effects meta-analyses ( n = 1, 388–1, 685). For example, a 1-year increase in AgeAccelPheno or AgeAccelGrim was associated with a 0.01 mL (95% confidence interval [CI]: 0.01, 0.02) or 0.03 mL (95% CI: 0.01, 0.05) lower mean FEV1 respectively. In NSHD, AgeAccelPheno and AgeAccelGrim at 53 years were associated with age-related decline in performance between 53 and 69 years as tested by linear mixed models ( p < .05). In a subset of NSHD participants ( n = 482), there was little evidence that change in any AgeAccel measure was associated with change in performance conditional on baseline performance. Conclusions: We found little evidence to support associations between the first generation of DNAm-based biomarkers of aging and age-related physical or cognitive performance in midlife to early old age. However, there was evidence that the second generation biomarkers, AgeAccelPheno and AgeAccelGrim, could act as makers of an individual's healthspan as proposed.